HISTORICAL WORKS COVER THE SOCIO-POLITICAL LIFE OF THE CENTRAL ASIAN KHANATES ON THE EVE OF THE INVASION OF THE RUSSIAN EMPIRE - Sultanova Maxfuza Ibroximovna (Galaxy International Interdisciplinary Research Journal, 2022)
The article covers the socio-political life of the khanates of Central Asia on the eve of the invasion of the Russian Empire, the attitude of the population to the policy of governance on the basis of the works of local historians and Russian politicians. Revolts in the city of Tashkent in the second half of the XIX century and their consequences are described.